2006
DOI: 10.1007/s00299-006-0144-3
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and field performance of Yucca valida

Abstract: Yucca valida is an important potential source of steroidal saponins closely related to Yucca schidigera, the species that is commercially exploited from the wild as a source of steroidal extracts. Neither of the species has been domesticated mainly because of their slow growth and long life span before harvesting. Here, we report a micropropagation method to generate isogenic or clonal lines for plantation purposes. Seventeen clonal lines were propagated and evaluated over a period of 26 months in an experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
1
6
2
Order By: Relevance
“…Since the micropropagated P. peltatum cultures have been maintained from the last 9 yr with subculture frequency every 2 mo, somaclonal mutation might have happened at multiplication phase during maintenance rather than in storage. With similar variations depending on the number of subcultures, the tissues had undergone mutations and have been reported by other researchers (Webster and Jones 1989;Hirochika et al 1996;Chaturvedi et al 2001;Arce-Montoya et al 2007). Also, there is a possibility that the stress imposed on explants may have resulted in this point mutation.…”
Section: Resultssupporting
confidence: 51%
“…Since the micropropagated P. peltatum cultures have been maintained from the last 9 yr with subculture frequency every 2 mo, somaclonal mutation might have happened at multiplication phase during maintenance rather than in storage. With similar variations depending on the number of subcultures, the tissues had undergone mutations and have been reported by other researchers (Webster and Jones 1989;Hirochika et al 1996;Chaturvedi et al 2001;Arce-Montoya et al 2007). Also, there is a possibility that the stress imposed on explants may have resulted in this point mutation.…”
Section: Resultssupporting
confidence: 51%
“…The average multiplication factor was 2.17 ± 0.35 shoots per explant and no significant differences were found between the clonal lines used (P > 0.05). These results differ from those from a larger sample of clonal lines generated from seed (Arce- Montoya et al 2006), where significant differences were observed in the morphogenic capacity between different clonal lines. In most cases no correlation was observed between the growth capacity of the mother plant and the proliferation capacity of the explants derived from them as it has been described in Ficus benjamiana where the high proliferation rate of a selected clone was shown to coincide with the fastest growth rate in the greenhouse (Kristiansen 1992).…”
Section: Resultscontrasting
confidence: 85%
“…For this purpose, we developed a protocol for the micropropagation of Y. valida plants from plants germinated from seeds in vitro (Arce-Montoya et al 2006). It was, however, necessary to adapt the methods for the establishment and micropropagation of in vitro cultures from selected plants growing in the field and to produce clonal lines from them to evaluate their performance.…”
Section: Introductionmentioning
confidence: 99%
“…In an experiment on Y. valida grown on a single plot of land using clones and seeds of different individuals (i.e. genotypes), Arce-Montoya et al (2006) found that there was a signifi cant difference in plant growth depending on genotype, indicating that there was genetic variation related to the development of the seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the production of fl owers represents the fi rst opportunity to produce offspring with genetic variation within populations. Considering that in an-other Yucca species it has been demonstrated that offspring derived from seed possess advantages in terms of growth compared to the offspring derived from asexual reproduction (Arce-Montoya et al, 2006), the occurrence and regularity of precipitation could play an important role in population dynamics through the contribution and formation of seeds, germination and the establishment of individuals with a different genetic constitution. Secondly, infl orescence production in conjunction with fruit production observed in some populations are clear evidence of the occurrence of the obligated Yucca-moth interaction.…”
Section: Discussionmentioning
confidence: 99%